Fiberoptic endoscopic findings of oropharyngeal swallowing of different food consistencies in amyotrophic lateral sclerosis - Gozzer, Marina Mendes [UNESP]; Cola, Paula Cristina [UNESP]; Onofri, Suely Mayumi Motonaga [UNESP]; Merola, Beatriz Novaes [UNESP]; da Silva, Roberta Gonçalves [UNESP] (FapUNIFESP (SciELO), 2020)
Purpose: This study aimed to compare the fiberoptic endoscopic findings of oropharyngeal swallowing of distinct food consistencies in Amyotrophic Lateral Sclerosis (ALS). Methods: This was a retrospective clinical study of a convenience sample of 20 individuals (13 males and seven females aged 34 to 78 years old) with a diagnosis of ALS and oropharyngeal dysphagia confirmed by clinical and objective evaluation of swallowing, regardless of the bulbar or skeletal type and of the time of neurological diagnosis. The fiberoptic endoscopic evaluation of swallowing (FEES) of the liquid (N = 18), thickened liquid (N = 19) and pureed samples (N = 20) in a volume of 5 ml were analyzed. Data related to posterior oral spillage, pharyngeal residues, laryngeal penetration and/or aspiration after swallowing the three food consistencies were analyzed statistically by the Friedman ANOVA test. Results: No impairment of laryngeal sensitivity was found in this population. There was no statistically significant difference in posterior oral spillage, penetration and/or aspiration between food consistencies. There was a statistically significant difference only related to pharyngeal residues of the thickened liquid and pureed consistency. Conclusion: Among the fiberoptic endoscopic findings of swallowing in ALS, only pharyngeal residues had a higher frequency depending on the consistency of food.
Keywords: Deglutition; Deglutition disorders; Endoscopy; Evaluation; Neurodegenerative diseases